The dynamic evolution of the characteristics of exchange rate risks in countries along "The Belt and Road" based on network analysis. - Zhewen Liao; Zhongxing Wang; Kun Guo (PLoS ONE, 2019)
As of November 1, 2018, China's "One Belt and One Road" Initiative has involved 123 countries and promoted worldwide communication, cooperation and trade exchange. This paper constructs correlation networks of exchange rates among the countries along "The Belt and Road" and analyzes the risk contagion structure. It is found that when "The Belt and Road" initiative is initialized, countries in Eastern Europe occupy important positions in the network and play a vital role in the spreading of exchange rate risks; however, during the process of "The Belt and Road" initiative, the exchange rate risks are decentralized geographically, whereas they are centralized in countries that have in-depth communication and cooperation. The minimum Spanning Tree method is also proposed to investigate the structure of complex networks. It is found that the geographical link between exchange rate fluctuations and correlations among the countries has been strengthened while China has become an important node in the exchange rate network after the launch of "The Belt and Road" initiative. In addition, the influence and promotion of RMB has rapidly benefited from the initiative.